Visual fatigue in congenital nystagmus caused by viewing images of color sequential projectors - Ogata, M.; Ukai, K.; Kawai, T. (Journal of display technology, 2005)
Color breakup is the perceived splitting of the white portions of an image into its red, green, and blue components when the image is projected with the color sequential method and the viewer is moving his or her eyes. This study aims to evaluate how color breakup affects symptoms of visual fatigue in people with congenital nystagmus. The eyes of people with congenital nystagmus continuously oscillate leading to color breakup without pause. One in every 1 500 persons is afflicted with congenital nystagmus. Many sufferers have almost no symptoms in daily life except for a mild deterioration of visual acuity. Five subjects with congenital nystagmus were shown a 15-min portion of a movie projected with three video projectors (one liquid crystal display (LCD) projector and two single-chip digital light processing (DLP) projectors). They were subjectively evaluated both pre- and post-viewing with a questionnaire listing visual fatigue symptoms. One subject was tested in an additional experiment using six more projectors. Results indicated that subjects with congenital nystagmus felt severe visual fatigue after they viewed images produced by color sequential projectors. Mechanism of the cause of visual fatigue is not clear in general and in color breakup in congenital nystagmus, however, it was clear that people with nystagmus felt continuing color breakup as a flickering image. Flickering light is a major cause of visual fatigue. Color sequential projectors are best avoided in public settings, such as classrooms, lecture theaters and conference sites.